Electrochemical DNA-nano biosensor for the detection of cervical cancer-causing HPV-16 using ultrasmall Fe₃O₄-Au core-shell nanoparticles - Rasouli, Elisa (2023)
This paper reports a label-free biosensor for detecting human papillomavirus type 16 (HPV-16). For this purpose, the surface of the screen-printed carbon electrodes (SPCEs) was coated with Fe3O4-Au core-shell nanoparticles (NPs) using a green and facile eco-friendly method. The modified surfaces of the electrodes were then functionalized with thiolated single-strand DNA (ssDNA) probe human papillomavirus (HPV) DNA sequences. Next, the hybridization events with the immobilized probe DNA were monitored by cyclic voltammetry (CV) and differential pulse voltammetry (DPV) using [Fe(CN)6]3‐/4− as the redox indicator. Our results demonstrate that the modified electrodes could distinguish the redox current signals of [Fe(CN)6] 3−/4− due to the absence/presence of the immobilized probe DNA. Furthermore, quantitative estimations of the concentration of the probe DNA were also possible. Optimal performance was obtained for probe DNA concentrations between 1 and 10 μM. The best performance of our HPV biosensor was obtained for probe DNA concentration of 5 μM, for which the limit of detection and sensitivity of our developed sensor resulted to be 0.1 nM and 2.4 μA/nM, respectively.